Revbelándonos’: un podcast que cuestiona creencias sociales - Hwang Cueva, Nicole Altemira (2022)
Revbelándonos Podcast bears this name with the purpose of alluding to the need to reveal (V) in the first instance, the social beliefs that are usually seen as unquestionable, in order to rebel (B) against to what is established and dispute what has been dictated as a categorical imperative. The purpose of this project is to offer a digital space where questioning is incited in order to contribute to the collective consciousness awakening. In other words, to question in community what society believes is evident because it is through questions that human beings evolve. And there is no evolution without revolution. The episodes last approximately 20-25 minutes and in turn, some episodes will include interviews with specialists on various topics. Finally, it is intended to collect the greatest amount of opinions and information through Instagram & Tik Tok, as they are two of the most interactive social networks used by our target audience. The main qualities of the podcast are based on the horizontal tone that will be maintained in the episodes, as well as solidarity with human diversity, empathy and interactivity with the public.